Model of relationship between e-counselling skills, e-counselling ethics and e-counselling limitations with counselling self-efficacy - Zainudin, Zaida Nor; Asri, Alia Sarah; Mohamad Yusop, Yusni; Ahmad, Nor Aniza; Hassan, Siti Aishah; Lee, Wei Rong (International Association of Computer Science and Information Technology (I A C S I T), 2022)
Despite the increasing number of e-counsellors, there is a lack of studies especially in the Malaysian context that highlight the skills and practices among e-counsellors and how these are linked to their perceptions when providing e-counselling. This study identifies the relationship between e-counselling skills, e-counselling ethics and e-counselling limitations with counselling self-efficacy among e-counsellors in Malaysia. A total of 159 e-counsellors from various institutions in Malaysia participated in this online survey study. The respondents were selected using the simple random sampling method. The Counselling Self-Estimate Inventory was adopted, and three self-constructed scales were employed for data collection purposes. Correlation analysis found that e-counselling skills (r = 0.597, p < 0.001), e-counselling ethics (r = 0.201, p < 0.001) and e-counselling limitations (r = -0.511, p < 0.001) were significantly correlated to counselling self-efficacy. The structural equation model analysis confirmed the model of relationship between e-counselling skills, e-counselling ethics, e-counselling limitations and counselling self-efficacy. From the three dimensions, e-counselling limitations predicted counselling self-efficacy the best (β value = -0.60), followed by e-counselling ethics (β value= 0.56) and e-counselling skills (β value= 0.18). The findings imply that the extent of e-counsellors’ perceptions on the limitations present in e-counselling play an important role to predict the variance in counselling self-efficacy among e-counsellors. Professional counselling bodies, supervisors and counsellor educators are urged to design a more comprehensive educational and training programme for counsellors. Both counsellor candidates and professional counsellors will benefit from this study as it provides insights for more effective implementation of e-counselling.